Managing A Crisis A Practical Guide - Curtin, T. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2005)
This new practical guide explains what makes a crisis and who are the key players. It shows the importance of prior preparation and testing so that the company fully understands the crisis management environment and the importance of communications. Also included are checklists that should form part of the company's crisis management handbook and discussion of training and learning opportunities. This is a fully comprehensive approach to crisis management planning and implementation.